1988
DOI: 10.1017/s0022112088002642
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics and structure of double-diffusive layers in sidewall-heating experiments

Abstract: The dynamics and structure of double-diffusive layers were studied experimentally by heating a linear stable solute gradient from a sidewall in a wide tank. The formation and subsequent development of the layers were investigated by various flow-visualization techniques, namely fluorescent dye, fluorescent particles and shadowgraph. Experiments were performed in order to determine the stability diagram of the flow, following in each experiment the phase trajectory of the system in the phase plane of thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
46
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 16 publications
11
46
0
1
Order By: Relevance
“…In particular, when assumptions of such a type were made by Tanny & Tsinober (1988), for the interpretation of their experimental data, and by Kerr (1989), theoretically, the critical values of the Rayleigh numbers obtained in both these works showed reasonable agreement with the marginal stability curve computed for an infinite vertical slot by Hart (1971) and Thangam et ale (1980). Moreover, a weakly nonlinear analysis by Kerr (1990), where the quasi static assumption was also made, demonstrated that, like in the results obtained by Hart (1973) for the slot, it is the subcritical bifurcation that is responsible for the onset of the layers in the single-side-wall heating problem.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…In particular, when assumptions of such a type were made by Tanny & Tsinober (1988), for the interpretation of their experimental data, and by Kerr (1989), theoretically, the critical values of the Rayleigh numbers obtained in both these works showed reasonable agreement with the marginal stability curve computed for an infinite vertical slot by Hart (1971) and Thangam et ale (1980). Moreover, a weakly nonlinear analysis by Kerr (1990), where the quasi static assumption was also made, demonstrated that, like in the results obtained by Hart (1973) for the slot, it is the subcritical bifurcation that is responsible for the onset of the layers in the single-side-wall heating problem.…”
supporting
confidence: 58%
“…These include Thorpe, H utt & Soulsby (1969), , Narusawa & Suzukawa (1981), Tanny & Tsinober (1988) and Schladow, Thomas & Koseff (1992). The first of these concentrated on the onset of convection in a vertical slot, while the last focussed on the effects of having a vertical temperature stratification in addition to the salt stratification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, there are lateral intrusions at depths of & % 2 % # " % 2 % m, linked to the descending plume of Mediterranean waters cascading down the slope (Özsoy et al, 1993;Özsoy and Beşiktepe, 1995). The DL-susceptible interior may favor DL convection over SF convection (Turner, 1978), in the context of side-wall buoyancy source (heat and salt) introduced into the stratified environment (Tsinober et al, 1983;Tanny and Tsinober, 1988). Boundary mixing driven by the doublediffusive convection (Özsoy et al, 1993;Özsoy and Beşiktepe, 1995), may be the dominant ventilation mechanism across the permanent halocline of the Black Sea, given the inferred transport of shelf-derived materials, including dissolved nutrients, Chernobyl tracers and inorganic particulates between surface and deep layers (Buesseler et al, 1991;Codispoti et al, 1991;Özsoy et al, 1991Buesseler and Livingston, 1997).…”
Section: Black Seamentioning
confidence: 99%
“…The subject of natural convection for single fluid flow and double diffusion has been studied extensively [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Yet, most work done considers flow inside closed enclosures.…”
Section: Introductionmentioning
confidence: 99%